Variación morfológica de plántulas e influencia del pH del agua de riego en doce poblaciones de Pinus greggii Engelm - López Upton, Javier; Mendoza Herrera, Adrián J.; Jasso Mata, Jesús; Vargas Hernández, J. Jesús; Gómez Guerrero, Armando (Instituto de Ecología, A.C., 2016)
A greenhouse study on sixteenmonth-old seedlings of Pinus greggii was carried out to determine whether geographic variation exists in relation to soil acidity. The study included five openpollinated families from each of twelve populations. Significant differences were found both among and within populations for seedling emergence, leaf color and total height. A pattern was detected in relation to geographic location. Northern populations as a group showed different treatment effects than the southern populations. This result agrees with information recently published in the description of a new variety of the species. Seedling height and leaf color were found to be under genetic control which may be useful for early selection of families within superior provenances.